EFFECTS OF ORGANIC PRODUCTS WITH INSECTICIDAL ACTION ON KEY INSECT PESTS IN ALFALFA SEED PRODUCTION - Nikolova, Ivelina Mitkova (Emirates Journal of Food and Agriculture, 2017)
A trial was conducted in the experimental field of the Institute of Forage Crops, Bulgaria, over the period 2012-2014 with alfalfa wich grew for seed production. It was studied the action of three insecticides (two biological /NeemAzal T/S and Pyrethrum FS EC/ and one synthetic insecticide Nurelle D - standard) to a control of lucerne seed weevil, Tychius flavus Beck. (Coleoptera: Curculionidae); alfalfa plant bug, Adelphocoris lineolatus Goeze (Hemiptera, Heteroptera: Miridae) and pea aphid, Acyrthosiphon pisum Harr. (Hemiptera, Sternorrhyncha: Aphididae) - major pests in alfalfa seed production. The method of sweeping with entomological net was used. Organic products were most effective against A. pisum. Increasing efficacy of NeemAzal reached satisfactory values of 67.8 and 69.1 percent of the seventh and ninth day after the application. Pyrethrum exhibited strong efficacy throughout the reporting period in the range 73.9-82.8% and differences between bioinsecticides were significant. In compared with standard its toxic action after the fifth day was approached the effect of synthetic insecticide with minor differences between them. Bioinsecticides exhibited good control against A. lineolatus as the trend of the better protective effect of Pyrethrum was retained. A dominant influence on the efficacy variation and seed productivity had the type of insecticide followed by factors year of treatment. The productivity of аlfalfa grown for seed production realized after application of Pyrethrum significantly exceeded control and was comparable to that of Nurelle D.